Legal Concerns in Classroom Management: Role of the Counsellor0 - Eberleinrg, Larry (Canadian Journal of Counselling and Psychotherapy, 2012)
Counsellors are expected to assist teachers in discipline and other classroom management problems. An awareness of potential civil and criminal legal responsibilities which affect educational staff is essential to proper planning strategies. Three basic sources of legal authority to control student behaviour are discussed as are court cases relating to improper discipline. While counsellors probably share a teacher's legal protection in a disciplinary situation, this is less clear when counsellors are involved in behavioural management programs. Suggestions are made for counsellor and teache action to achieve desired classroom goals while still protecting student and parental rights to freedom from unlawful interference with the person or invasion of family privacy. Examples of both positive and negative reinforcement and punishment are considered, and the legal implications of each are discussed.